Braiding frameworks for collaborative stewardship scholarship - Carney, Molly (Frontiers in Environmental Archaeology, 2024)
Human-environment relationships are most frequently viewed from evolutionary perspectives, despite the vast body of literature which highlights how many Indigenous peoples engage with and understand place, plants, and animals as kinship relations. My goals in this essay are twofold: first, to suggest we adopt the phrase stewardship to recognize and uphold notions of respect, reciprocity, and relationships that are common within many Indigenous worldviews, and secondly, to advocate for the use of pluralistic approaches to our collaborative scholarship. I offer examples from my own experiences in reconstructing stewardship histories across people, plants, and places in the Pacific Northwest.